Planejamento de cidades inteligentes: uma análise dos planos diretores dos municípios brasileiros - Batista, Giseli Quirino (2021)
Smart cities have been highlighted in the media, in international rankings and in studies and scientific research, due to their solutions to the various urban problems, as well as the positive results in indicators, economic, social, environmental, etc. In Brazil there are already cities that are developing actions and strategies with the objective of becoming more "intelligent". However, it is necessary to have an integrated planning that considers the dimensions, characteristics, needs and demands of each Brazilian city and that results in sustainable actions and a better quality of life for the entire population. The Municipal Master Plan (MMP), as the main instrument of planning and urban policy in Brazilian cities, can and should be used to promote and stimulate the development of smart cities in Brazil. Therefore, the objective of this study is to identify the contributions of MMPs to the development of smart cities in Brazil. To this end, 186 MMPs were collected, being 26 capital cities, the Federal District (Brasília) and 159 municipalities from all regions and states of Brazil. To analyze the documents, I employed a Topic Modeling technique, making possible to identify the underlying latent topics in the MMPs: (1) Sustainability, that discusses the development of public policies related to economic, social and environmental issues; (2) Zoning, which addresses issues, land use and occupation, and zoning; (3) Urban mobility, comprised of essential services, more specifically in the field of transportation infrastructure; and (4) Delimitation of streets and avenues, that defines the urban perimeter in cities and delimitation of the territory, as well as the naming of neighborhoods, streets, avenues, zip codes (postal code addressing). However, when observing other indicators such as economy, education, and health, it was found that the MMPs lacks effectiveness in the proposed actions, as it has not been able to regularly supply the needs and demands of the population and the municipality. The main contributions of this study are: (1) bring to the urban planning area an innovative and evidence-based method (Topic Modeling), which should be used in other studies and research; (2) the extensive and detailed analysis of the sample containing 186 MMPs, allowed to observe the structure, conformation, latent topics (contents) and effectiveness of these master plans in the face of demands and economic, education and health indicators; (3) to place MMPs as an important instrument for the development of smart cities in Brazil.